Self‐Assembled On‐Chip‐Integrated Giant Magneto‐Impedance Sensorics. (23rd September 2015) - Karnaushenko, Daniil; Karnaushenko, Dmitriy D.; Makarov, Denys; Baunack, Stefan; Schäfer, Rudolf; Schmidt, Oliver G.
Abstract : A novel method relying on strain engineering to realize arrays of on‐chip‐integrated giant magneto‐impedance (GMI) sensors equipped with pick‐up coils is put forth. The geometrical transformation of an initially planar layout into a tubular 3D architecture stabilizes favorable azimuthal magnetic domain patterns. This work creates a solid foundation for further development of CMOS compatible GMI sensorics for magnetoencephalography.